The Effect of Students’ Interest in English Song on the Value of Learning Outcomes in English Subject for Class VIII of SMP Negeri 1 Haurgeulis - Kunah, Kunah; Supriyani, Supriyani; Alamsyah, Marshus (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
This research aims to (1) help increase students' learning motivation in English subjects by growing students' interest in English songs (2) obtain evidence that the singing method can improve student learning outcomes in English subjects. To find out whether this method is effective or not, the author used pre-experimental research with a quantitative approach. The research was carried out using stages: Pre-test, Treatment and Post-test. Because the method used is a quantitative approach, to analyze the data the author used Linear Product Moment Regression Analysis, while to test the effect of treatment on the sample the authors used the paired sample t test. The results of data analysis show that the correlation coefficient value rxy is 0.659. This means that the regression correlation coefficient value of students' interest in English songs is 0.659, which has a positive sign, meaning that the higher the students' interest in English songs, the higher the students' interest in English songs student learning outcomes will be. The validity test results of all questionnaire items have Pearson Correlation ® values > 0.3494 then it can be concluded that all items are valid. Meanwhile, the results of the reliability test used Cronbach Alpha with a value of 0.839 > 0.6, which means that the questionnaire items in the instrument were reliable for use. From the results above, the hypothesis states Student’s interest in English Songs can improve the value of learning outcomes in English Subjects for class VIII of SMP Negeri 1 Haurgeulis can be accepted